Digital-Based Innovation in Islamic Education: Strategi Pembelajaran PAI da-lam Meningkatkan Student Engagement di Era Society 5.0 - Nur Azizah; Slamet Faturrohman; Kamaliya Ramadhani; Faza Muna Najiah Nubari; Mamun Hanif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of Society 5.0 encourages the integration of digital technology into Islamic Religious Education (PAI). However, PAI learning is still often dominated by conventional methods that reduce student engagement. This study aims to analyze digital-based innovations in PAI learning and formulate strategies to improve student engagement in the Society 5.0 era. Using a descriptive qualitative literature review method, data were collected from relevant journals, books, and academic publications. The findings show that digital innovations such as gamification, Artificial Intelligence (AI), Augmented Reality (AR), Learning Management Systems (LMS), and interactive media can enhance students’ cognitive, emotional, and behavioral engagement. This study also proposes the ECOPAI 5.0 model consisting of Engage, Connect, Organize, Personalize, Assess, and Internalize stages as a strategic framework for integrating technology and Islamic values in PAI learning.